On the dilemmatic creole condition : identity building and strategies of survival and catharsis in some poetry of Macau - Vera Borges (Études romanes de Brno)
The condition of Creole communities is per se dramatic and dilemmatic, if one considers them in the perspective of H. Bhabha (1998), as culturally hybrid, "interstitial" societies, emerging in contact zones, as defined by Pratt (2008) in a colonial context. Macao would function as one of these "n-between places". The already originally contradictory and ambiguous Macanese condition was agonizingly put to the test in the context of the ending of colonial empires, by the events that shaped the 20th century, with the announced return of Macao to China. We will consider the moments of reflection on identity building in various poetic voices stemmed from the Macanese community. From this enquiry it will become apparent that strategies of survival and catharsis are deeply embedded in poetic diction dealing with Macanese identity.